A Patient with Complex Gout with an Autoinflammatory Syndrome and a Sternoclavicular Joint Arthritis as Presenting Symptoms - M. M. Fedeli; M. Vecchi; P. Rodoni Cassis (Case Reports in Rheumatology)
A 50-year-old man presented to the emergency department with widespread pain, especially at the chest level, fever, and night sweats. Physical examinations revealed a swelling with localized pain in the left sternoclavicular joint. Laboratory tests showed a CPR of 134 mg/l and an ESR of 70 mm/h. The patient’s anamnesis is, for a chronic gouty arthritis, poorly controlled type 2 diabetes and a lumbosacral radicular syndrome. Home therapy includes metformin, sitagliptin, gliclazide, naproxen with partial benefit on pain, and febuxostat. Differential diagnoses of sternoclavicular swelling include infection, crystal or psoriatic arthropathy, tumor pathology, SAPHO syndrome, and osteoarthritis. An ultrasound scan performed at the thoracic level showed the presence of effusion in the sternoclavicular joint. A thoracoabdominal CT scan, performed in doubt of neoplasias, shows no masses but osteostructural nonspecific alterations of the sternoclavicular joint. We performed a dual energy CT (DECT) which reports a gouty arthropathy at the sternoclavicular joints (in the literature, only three similar cases are proved). Because of the poor therapeutic effects using febuxostat and systemic corticosteroids, the patient was treated with anakinra, an interleukin 1 receptor antagonist, which led, 6 months after the event, to a total remission.